(untitled) (Journal of Informatics and Mathematical Sciences, 2017)
In this paper using the concept of fuzzy b-open (fuzzy b-closed)sets to introduce some new types of intuitionistic fuzzy b separation axioms, intuitionistic fuzzy b-Ti space (for \(i = 3, 4\)) and (intuitionistic Fuzzy b-Regular and b-normal) spaces are introduced. Some theorems about them are investigated. Stronger forms of (intuitionistic fuzzy b-regular) and (intuitionistic fuzzy b-normal) spaces are introduced. Moreover, the relationships between these separation axioms and others are investigated.